La vitesse dans les shoot ' em up: Accélérer et ralentir la matière numérique. - Baldisseri, Giacomo (Études Digitales, 2023)
The article focuses on the practice of speedrunning in shoot 'em up (shmup) games, particularly on how players can influence the speed of the game despite the automatic scrolling. It explores how players can manipulate the speed of their avatar and the rhythm of the game through specific strategies, such as weapon choices or enemy management, to optimize their performance. The author also emphasizes the importance of the machine's processing power and how slowdowns can be used for aesthetic purposes, transforming technical limitations into gameplay elements. Finally, the article invites reflection on the nature of autoscrolling and its interaction with player actions, suggesting that this dynamic deserves further analysis.